Overexpression of Diacylglycerol Acyltransferase-1 Reduces Phospholipid Synthesis, Proliferation, and Invasiveness in Simian Virus 40-transformed Human Lung Fibroblasts - Bagnato, Carolina (2003)
Diacylglycerol (DAG) is a versatile molecule that participates as substrate in the synthesis of structural and energetic lipids, and acts as the physiological signal that activates protein kinase C. Diacylglycerol acyltransferase (DGAT), the last committed enzyme in triacylglycerol synthesis, could potentially regulate the content and use of both signaling and glycerolipid substrate DAG by converting it into triacylglycerol. To test this hypothesis, we stably overexpressed the DGAT1 mouse gene in human lung SV40-transformed fibroblasts (DGAT cells), which contains high levels of DAG. DGAT cells exhibited a 3.9-fold higher DGAT activity and a 3.2-fold increase in triacylglycerol content, whereas DAG and phosphatidylcholine decreased by 70 and 20%, respectively, compared with empty vector-transfected SV40 cells (Control cells). Both acylation and de novo synthesis of phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin were reduced by 30-40% in DGAT cells compared with controls, suggesting that DGAT used substrates for triacylglycerol synthesis that had originally been destined to produce phospholipids. The incorporation of [14C]DAG and [ 14C]fatty acids released from plasma membrane by additions of either phospholipase C or phospholipase A2 into triacylglycerol was increased by 6.2- and 2.8-fold, respectively, in DGAT cells compared with control cells, indicating that DGAT can attenuate signaling lipids. Finally, DGAT overexpression reversed the neoplastic phenotype because it dramatically reduced the cell growth rate and suppressed the anchorage-independent growth of the SV40 cells. These results strongly support the view that DGAT participates in the regulation of membrane lipid synthesis and lipid signaling, thereby playing an important role in modulating cell growth properties.